Potential Benefits of Combined Statin and Metformin Therapy on Resistance Training Response in Older Individuals - Long, Douglas E.; Kosmac, Kate; Dungan, Cory M.; Bamman, Marcas M.; Peterson, Charlotte A.; Kern, Philip A. (Frontiers in Physiology, 2022)
Metformin and statins are currently the focus of large clinical trials testing their ability to counter age-associated declines in health, but recent reports suggest that both may negatively affect skeletal muscle response to exercise. However, it has also been suggested that metformin may act as a possible protectant of statin-related muscle symptoms. The potential impact of combined drug use on the hypertrophic response to resistance exercise in healthy older adults has not been described. We present secondary statin analyses of data from the MASTERS trial where metformin blunted the hypertrophy response in healthy participants (>65 years) following 14 weeks of progressive resistance training (PRT) when compared to identical placebo treatment (n = 94). Approximately one-third of MASTERS participants were taking prescribed statins. Combined metformin and statin resulted in rescue of the metformin-mediated impaired growth response to PRT but did not significantly affect strength. Improved muscle fiber growth may be associated with medication-induced increased abundance of CD11b+/CD206+ M2-like macrophages. Sarcopenia is a significant problem with aging and this study identifies a potential interaction between these commonly used drugs which may help prevent metformin-related blunting of the beneficial effects of PRT. Trial Registration: ClinicalTrials.gov, NCT02308228, Registered on 25 November 2014.